Measuring Districts' Monthly Economic Activity from Outer Space - Beyer, Robert C. M.; Chhabra, Esha; Galdo, Virgilio; Rama, Martin (World Bank, Washington, DC, 2018)
Evening-hour luminosity observed using satellites is a good proxy for economic activity. The strengths of measuring economic activity using nightlight measurements include that the data capture informal activity, are available in near real-time, are cheap to obtain, and can be used to conduct very spatially granular analysis. This paper presents a measure of monthly economic activity at the district level based on cleaned Visible Infrared Imaging Radiometer Suite nightlight and rural population. The paper demonstrates that this new method can shed light on recent episodes in South Asia: first, the 2015 earthquake in Nepal; second, demonetization in India; and, third, violent conflict outbreaks in Afghanistan.